Smoking cessation treatment for individuals with comorbid diabetes and serious mental illness in an integrated health care delivery system. (March 2021) - Hwong, Alison R.; Schmittdiel, Julie; Schillinger, Dean; Newcomer, John W.; Essock, Susan; Zhu, Zheng; Dyer, Wendy; Young-Wolff, Kelly C.; Mangurian, Christina
Highlights: Smokers with type 2 diabetes and serious mental illness (SMI) studied. SMI group more likely to fill smoking cessation prescriptions than non-SMI group. Primary care providers wrote 80% of smoking cessation medication prescriptions. Mental health providers wrote fewer than 9% of smoking cessation prescriptions. Abstract: Introduction: Smoking is a significant modifiable risk factor for mortality for persons with serious mental illness (SMI), who have a life expectancy 15–20 years shorter than the general population. Individuals with SMI and comorbid diabetes who are smokers face an even higher risk of cardiovascular complications and early death. Yet despite high rates of smoking among people with SMI, tobacco cessation interventions have not been broadly offered to this population. Methods: We conducted a retrospective cohort study using electronic health records from 2014 in a large integrated care delivery system to examine whether use of smoking cessation pharmacotherapy among smokers with type 2 diabetes varies by serious mental illness (SMI) diagnosis. We analyzed smoking cessation medication prescription fills among adult smokers with diabetes, comparing those with SMI (N = 634) and without SMI (N = 18, 021). Risk ratios were adjusted for age, gender, race, urban area type, and medical facility. Results: Of the SMI group, 19.09% filled at least one smoking cessation prescription compared to 9.73% of the non-SMI group (adjusted risk ratio 1.80 [95% CI 1.52–2.13]; p  < .001). For the SMI group, primary care providers wrote 80.24% of prescriptions, while psychiatrists wrote 8.81% of prescriptions. Conclusions: These findings offer an example of a delivery system with higher uptake of smoking cessation pharmacotherapy among people with SMI than without SMI, and highlight the opportunity to provide more smoking cessation interventions in mental health care settings.